Developing evidence based practice skills in youth justice - Trotter, Chris (European journal of probation, 2023)
A number of studies have found that when probation officers, and others who supervise young people and adults on community based orders, have good intervention skills their clients are more likely to be engaged in supervision and to have low recidivism rates. The skills include, role clarification, pro-social modelling, problem solving, cognitive and relationship skills. Little research has been done, however, on the development of these skills across whole organisations. This study aimed to examine the extent to which training and coaching of probation officers, across two state youth justice departments in Australia, improved the use of workers’ skills. Audio-tapes of worker/client interviews were provided to research staff before and after training and coaching. Analysis of the audio-tapes found a significant increase in the overall use of worker skills following the training and coaching. However, the increases in the skills applied largely to role clarification, rather than pro-social modelling, problem solving and cognitive skills.